Community Understandings of Childhood Transitions in Ethiopia: Different for Girls - Camfield, L; Tafere, Y (Taylor and Francis, 2011)
The paper explores the perspectives of caregivers and other adults on the nature and timing of childhood transitions, elicited through group discussions in five Ethiopian communities, as reflective of the community norms that shape childhood transitions. The paper uses data from Young Lives, a longitudinal study of children growing up in poverty, to investigate the transitions made by girls from childhood to the onset of puberty. It argues that these transitions are rarely linear, singular, or focused on ‘learning’, but instead multiple and often contradictory. While girls are said to be constrained by lack of opportunities, the main constraint to successful transitions in the communities discussed in the paper is having too many potentially contradictory opportunities, too soon.